The Progressive Palatalization and the Old Novgorodian Pronoun vъxe - Галинская, Елена Аркадьевна Аркадьевна (Slavistica Vilnensis, 2015)
The progressive palatalization is one of the most debatable questions of the historical Slavic linguistics. For instance, there is no plausible explanation for the Old Novgorodian pronoun vъxe which does not exhibit the effect of the progressive palatalization. It is attested 23 times in the Novgorodian birch bark letters and in Varlaam’s letter. In 17 cases, there is Ъ in the root, in 5 cases the root has no vowel, and only in one birch bark letter there is Ь in the root. The latter text was written after the fall of yers which makes it possible that Ь marks the assimilative palatalization of [v]. I propose a possible explanations for this situation and argue that Ъ in the root predates the split-off of the Novgorodian dialect from Common Slavic. It is a plausible hypothesis since there are Novgorodian phenomena which came into existence during the Common Slavic period and are unattested in other Slavic dialects. If it is so, there is no need to expect the progressive palatalization in the root vъx- because there were no conditions for that, as there is no front vowel before x.
Keywords: the historical Slavic linguistics; the progressive Palatalization; old Novgorodian dialect; birch bark letters; the Common Slavic; pronoun vъxe